2020
DOI: 10.1136/bmjopen-2019-033761
|View full text |Cite
|
Sign up to set email alerts
|

Trends in healthcare use in children aged less than 15 years: a population-based cohort study in England from 2007 to 2017

Abstract: ObjectiveTo describe changing use of primary care in relation to use of urgent care and planned hospital services by children aged less than 15 years in England in the decade following major primary care reforms from 2007 to 2017DesignPopulation-based retrospective cohort study.MethodsWe used linked data from the Clinical Practice Research Datalink to study children’s primary care consultations and use of hospital care including emergency department (ED) visits, emergency and elective admissions to hospital an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 23 publications
4
55
0
Order By: Relevance
“…The past two decades have witnessed major changes in the lives of UK children and young people (CYP) and major increases in use of health services, particularly emergency services 1 . There have also been a number of broader changes in patterns of disease in these age-groups.…”
Section: Introductionmentioning
confidence: 99%
“…The past two decades have witnessed major changes in the lives of UK children and young people (CYP) and major increases in use of health services, particularly emergency services 1 . There have also been a number of broader changes in patterns of disease in these age-groups.…”
Section: Introductionmentioning
confidence: 99%
“…Low health literacy has been found to be a factor in parental overestimates of child illness severity, increased urgency for seeking care, and increased use of emergency services [6,7]. There has been an increase in the use of urgent hospital services by children and infants across England in the past decade, including for nonurgent presentations [8][9][10]. Emergency services are more frequently used by children and young people than adults [8,11].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…A review of factors affecting these behaviors found a range of different reasons, including (among others): parents' uncertainty and lack of confidence around recognizing problematic symptoms or evaluating their child's condition; mistrust of, or previous negative experiences with, clinicians; concerns about wasting clinicians' time; and being perceived negatively by clinicians [20]. This demonstrates the need for better access to primary care services or community-based support for acute pediatric illness and efforts to improve parental health literacy and confidence in determining whether, or which, treatment services are appropriate when a child is ill and how best to manage acute childhood illnesses [1,10,13]. This is particularly relevant in the current context of the COVID-19 pandemic, which has increased the burden on health care services.…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 10% of infants attending an ED in a large district general hospital had no coded diagnosis and probably attended for minor illness and general advice only [9]. As this is a growing proportion of ED attendances, this puts a lot of demand on our health services [10]; greater use of community pharmacy services instead of medical services for minor ailments could help relieve pressure on healthcare providers in high-cost settings [11,12].…”
Section: Introductionmentioning
confidence: 99%